Aesthetic Concerns of Chin Augmentation With Hyaluronic Acid Soft Tissue Filler in Chinese: A Prospective, Observational Study. Issue 3 (13th March 2023) - Li, Xin-Rui; Hong, Wei-Jin; Li, Zhen-Hao; Luo, Cheng-En; Jiang, Xuan-Yu; Luo, Sheng-Kang
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: The chin is an important facial structure that directly affects the overall contour of the face. The key to achieving a beautiful, effective, and safe chin injection is to make a good facial assessment and use an appropriate injection technique to achieve the best injection effect. OBJECTIVE: In this article, the authors will discuss cosmetic concepts for the chin area and verify the effectiveness of chin augmentation techniques. MATERIALS AND METHODS: Chin volume injections were performed on 23 Asian female subjects and 15 Asian male subjects. Demographic and imaging data were collected, and the facial aesthetic length was calculated. The authors also measured the length of beautiful chins, as evaluated by 2 plastic surgeons, and the ratios of chins from "The 100 Most Beautiful/Handsome Faces in China" published by TCC Asia in 2020. RESULTS: The mean volume of chin filling was 1.89 ± 0.74 mL in female subjects and 2.68 ± 1.28 mL in male subjects. The ideal length of the chin was equal to that of the nasal dorsum in male subjects, and the ideal chin-to-nasal dorsum ratio was 0.9 in female subjects. CONCLUSION: In this study, the authors investigate sex differences in chin aesthetics among the Chinese population and introduce an aesthetic and anatomical approach to chin injection.